EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMA NEGERI 1 ANGKOLA BARAT - Nanda Sri Alfina Nasution; Rahmatika Elidra; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The aim of this study is to describe the effectiveness of using flipped classroom learning model on students' critical mathematical thinking ability of SMP Negeri 1 Angkola. The research was conducted by applying experimental method (one group pretest post test design) with 30 students as the sample and they were taken by using cluster random sampling technique from 180 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using flipped classroom was 3.67 (good category) and (b) the average of students' critical mathematical thinking ability before using flipped classroom learning model was 50.53 (fair category) and after using 88.40 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 22), the result showed the significant value was less than 0.05 (0.000<0.05). It means, using flipped classroom learning model was effective on students' critical mathematical thinking ability of SMP Negeri 1 Angkola.